Cryptococcus neoformans phospholipase B1 is critical for cryptococcoma formation in the mouse brain - Munzen, Melissa E.; de Sousa Araújo, Glauber R.; Hamed, Mohamed F.; Reguera-Gomez, Marta; Lee, Hiu Ham; Pontes, Bruno; Alviña, Karina; Frases, Susana; Martinez, Luis R. (Frontiers in Immunology, 2025)
BackgroundCryptococcus neoformans (Cn) is an encapsulated, neurotrophic fungus that can cause life-threatening meningoencephalitis in immunocompromised individuals. Phospholipase B1 (PLB1) promotes Cn adhesion and colonization, however its role in fungal biofilm formation is not entirely clear.MethodsWe investigated how PLB1 is involved in Cn infection using a stereotaxic intracerebral infection mouse model, microscopy, whole-genome sequencing, and biophysical methods.ResultsOur results showed that the PLB1-disrupted strain exhibited reduced survival and capsular polysaccharide (CPS) dissemination throughout brain tissue and elicited a stronger microglial response in vivo. Moreover, Cn adhesion to SH-SY5Y human neuroblastoma cells was weakened in the PLB1-disrupted strain, and in vitro biofilm formation showed reduced metabolic activity and thickness. Both the PLB1-disrupted and -reconstituted strains showed structural alterations; nevertheless, CPS production was increased in the PLB1-disrupted cells. We show that PLB1 is essential for maintaining capsular elasticity, regulating CPS secretion, and biofilm formation, which are critical for fungal colonization and cryptococcoma formation.ConclusionThese results emphasize the need for further investigation into the mechanisms underlying the pathogenicity of Cn. In addition, our findings provide further evidence to validate PLB1 as an important antifungal target.